Utilización de dos niveles del tubérculo papa china (Colocasia esculenta) en la alimentación de cerdos en la etapa de crecimiento y engorde en la provincia de Santo Domingo de los Tsáchilas - Velásquez Pincay, Hernán Roberto (2015)
In Ecuador, the rates for pig production are very high so it is necessary to provide food that meets the nutritional requirements of the different stages according to the age of the animal at minimal cost to optimize production efficiency. The aim of this study was to use the “papa China” tuber levels of 10% to 20% in pig feed in stages of growth and fattening. Production parameters evaluated were weight gain, feed intake, feed conversion to determine the best levels of “papa China” in feed for pigs and perform cost / benefit based on partial costs. The results were satisfactory in the case of this new animal feed which gave us a significant feed conversion compared with commercial feed. When variables of weight gain and fattening were examined, the results for the best conversion obtained was the T2, with the supply of a balanced meal containing 20% the “papa China” which averaged 2.05 weight gain....